The Pattern of Building Character for Students in Salaf and Modern Islamic Boarding Schools at East OKU Regency South Sumatra Province - Ahmad Munawir; Kasinyo Harto; Nur Laila (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Character education has became a critical issue amid the moral degradation of the younger generation, such as the prevalence of brawls and behaviors that deviate from norms. Islamic boarding schools, as Indonesia's oldest Islamic educational institutions, play a strategic role in shaping students' character through traditional (salaf) and modern approaches. This study compares the character-building patterns of students at the Salaf Darul Falah Tulungsari Islamic Boarding School and the Modern Nurussalam Sidogede Islamic Boarding School in OKU Timur Regency to understand their characteristics, methods, and impacts on forming noble character. This study aims to: analyze the fundamental characteristics of both pesantren, identify the character-building patterns for students in each pesantren, and compare the character-building patterns to reveal similarities, differences, and their effectiveness in shaping students with noble character, discipline, and relevance to contemporary needs. This study employs a qualitative approach with a comparative case study design. Data were collected through observation, interviews with pesantren leaders, teachers, and students, and documentation, including vision-mission statements, organizational structures, and activity photos. Data analysis was conducted descriptively and comparatively to identify the characteristics and patterns of character building in both pesantren. The Salaf Darul Falah Islamic Boarding School implements a dual education system (classical and salaf) focusing on classical Islamic texts (kitab kuning) using sorogan and bandongan methods, alongside a culture of mutual cooperation (ro’an) based on the values of Iman-Islam-Ihsan. Character building is carried out through exemplary behavior of the kiai, habituation, and strict supervision, producing students with noble character, discipline, and a strong religious identity. Conversely, the Modern Nurussalam Islamic Boarding School adopts the KMI curriculum, integrating religious and general knowledge with a 24-hour holistic approach, using formal (lectures, discussions) and informal (habituation, exemplary behavior) methods, and emphasizing the Panca Jiwa culture of discipline and leadership. This results in students who are globally aware, independent, and ready to be agents of change. The comparison shows that both approaches complement each other, with Darul Falah excelling in religious tradition and Nurussalam in modern adaptation, both effectively shaping character in line with their respective visions.